2014
DOI: 10.1038/gt.2014.103
|View full text |Cite
|
Sign up to set email alerts
|

AAVrh.10 immunogenicity in mice and humans. Relevance of antibody cross-reactivity in human gene therapy

Abstract: Simian adeno-associated virus (AAV) serotype rh.10 is a promising gene therapy tool, achieving safe, sustained transgene expression in the nervous system, lung, liver and heart in animal models. To date, preexisting immunity in humans has not been confirmed, though exposure is unexpected. We compared the humoral immune response with serotypes AAVrh.10 and AAV9 in mice, and AAVrh.10, AAV9 and AAV2 in 100 healthy humans. Mice, injected-intravenously, raised significantly more anti-AAV9 than anti-AAVrh.10 IgG (im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
58
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(60 citation statements)
references
References 32 publications
1
58
1
Order By: Relevance
“…12,15,16 These findings differ from observations in gene therapy trials, in which a replication-deficient serotypespecific AAV vector is injected into subjects with no preexisting AAV NAbs, in which the ensuing NAb response is limited to the AAV serotype that was injected. 17,18 To further understand the phenomenon of naturally occurring broadly cross-neutralizing NAb responses observed in nonhuman primates, we conducted a longitudinal study designed to analyze serum samples collected from captive housed chimpanzees over 10 years for AAV NAbs.…”
Section: Introductioncontrasting
confidence: 73%
“…12,15,16 These findings differ from observations in gene therapy trials, in which a replication-deficient serotypespecific AAV vector is injected into subjects with no preexisting AAV NAbs, in which the ensuing NAb response is limited to the AAV serotype that was injected. 17,18 To further understand the phenomenon of naturally occurring broadly cross-neutralizing NAb responses observed in nonhuman primates, we conducted a longitudinal study designed to analyze serum samples collected from captive housed chimpanzees over 10 years for AAV NAbs.…”
Section: Introductioncontrasting
confidence: 73%
“…The cumulative safety experience with the rapidly growing number of AAV-based trials targeting the human liver, combined with the low rate of HCC-associated AAV integrations despite the high seroprevalence of wild type AAV in the human population (e.g. >50% for AAV2) (Thwaite et al 2015) are consistent with a favourable safety profile of AAV vectors. Nevertheless the findings of Nault et al warrant further studies and mandate close monitoring in ongoing human trials.…”
Section: Current Challengesmentioning
confidence: 87%
“…Studies in humans have found that antibodies to some AAV serotypes are less prevalent than others. 50 AAV serotype switching and capsid engineering strategies have produced promising results. 51,52 Because the capsid composition is different between rAAV RD and rAAV HD particles, it can be hypothesized that humoral immunity may also have some difference.…”
Section: Discussionmentioning
confidence: 99%